The role of metal-halide bond in the distortions and asymmetric non-covalent interactions in chiral hybrid perovskites - Mariagrazia Fortino; Alessandro Mattoni; Adriana Pietropaolo (JPhys Materials)
Hybrid organic–inorganic perovskites have become interesting materials with a set of applications spanning from optoelectronics to energy conversion technologies. Recently, chiral hybrid perovskites encapsulating chiral organic ligands into the inorganic framework, have garnered significant attention for their promising potential in chiroptoelectronics. The generation of chirality and the corresponding chiroptical response are attributed to a chiral bias that arises from the chiral organic ligands extending into the inorganic framework. This was proposed to affect the inorganic geometry, propagating within the whole hybrid perovskite scaffold. Herein, we aim at clarifying the connection between coordination geometries and their distortions in chiral perovskites, by comparing tin and lead 2D perovskites encapsulating chiral methyl benzyl ammonium, S-(MBA ^+ ) _2 PbI _4 and S-(MBA ^+ ) _2 SnI _4 . Ab-initio molecular dynamics simulations based on density functional theory methods were used and disclosed higher degrees of distortion for the tin-based chiral HOIP model, with prominent alteration of the equatorial coordination and evident bending of the equatorial angle. Such geometrical distortions stabilize non-covalent CH- π interaction observed in the tin-based chiral perovskite in which reduced ligand–ligand distances have been found during the dynamics. The substitution of lead with tin ions within the crystallographic coordinates of S-(MBA ^+ ) _2 PbI _4 maintains the same degree of distortion observed in S-(MBA ^+ ) _2 SnI _4 . This result indicates that the central metal strongly influences the overall packing encapsulating the chiral ligands stabilized by non-covalent interactions. The more the central metal is a hard acid, the more the bond with the soft iodide base is weak or viceversa the more the central metal is a soft acid, the more the bond with a hard base is weak. The weakeness of the metal-halide bond increases the distortion and asymmetric non-covalent interactions within the chiral perovskite scaffold.